2019
DOI: 10.3390/ma12091482
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a Ti–Cu Alloy with Carbon: Synthesis of Composites and Model Experiments

Abstract: Titanium carbide (TiC), is the most thermodynamically stable compound in the Ti–C–Cu system, which makes it a suitable reinforcement phase for copper matrix composites. In this work, the interaction of a Ti–Cu alloy with different forms of carbon was investigated to trace the structural evolution leading to the formation of in-situ TiC–Cu composite structures. The reaction mixtures were prepared from Ti25Cu75 alloy ribbons and carbon black or nanodiamonds to test the possibilities of obtaining fine particles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This reaction can be regarded as the "dissolution" process of the solid phase in the liquid phase. It was found in the experiment that, during the reaction, a TiC x transition layer forms on the surface of the solid C source particles, which was also found in the study of Dudina et al [26] when investigating the solid-state interactions in the Ti 25 Cu 75 + C system with different sources of carbon. For a solid C particle wrapped by solid TiC x , if the reaction interface is between the liquid alloy and the TiC x layer and the reaction is determined by the diffusion of C, then the volume of the solid C should decrease gradually, and there will be a gap between the solid particle and the layered TiC x .…”
Section: Basic Assumptionssupporting
confidence: 71%
See 1 more Smart Citation
“…This reaction can be regarded as the "dissolution" process of the solid phase in the liquid phase. It was found in the experiment that, during the reaction, a TiC x transition layer forms on the surface of the solid C source particles, which was also found in the study of Dudina et al [26] when investigating the solid-state interactions in the Ti 25 Cu 75 + C system with different sources of carbon. For a solid C particle wrapped by solid TiC x , if the reaction interface is between the liquid alloy and the TiC x layer and the reaction is determined by the diffusion of C, then the volume of the solid C should decrease gradually, and there will be a gap between the solid particle and the layered TiC x .…”
Section: Basic Assumptionssupporting
confidence: 71%
“…The one-step preparation of composite materials can be achieved via in situ reaction [22,23], which can help obtain a high interface bonding strength between the TiC x particles and the matrix metal [24]. Compared with ex situ processing techniques, synthesis approaches based on the in situ formation of particles in metal matrixes offer more possibilities to control the particle size and particle distribution pattern in the composites [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The NPT equations of motion were integrated using a leapfrog Verlet algorithm . The selected pressure was in line with experimental conditions for Cu–Ti alloys . Previous MD studies in polycrystalline metals, including Cu, have demonstrated that thermally annealing for 250 ps at 0.3–0.5 of the melting temperature of the metal promotes structural relaxation of the grains without allowing excessive grain growth .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, preliminary activated powders can be used not only for combustion synthesis, but also for reaction sintering, which is based on the idea of simultaneous synthesis and compaction of the material. This method produces a wide range of materials: composites [ 27 , 28 , 29 , 30 ], thermoelectrics [ 31 , 32 , 33 , 34 ], and ceramics [ 35 , 36 , 37 ], including high-entropy ones [ 38 , 39 , 40 , 41 ]. The implementation of this method is typically carried out on hot pressing (HP) and spark plasma sintering (SPS) devices and referred to as RHP and RSPS, respectively [ 42 ].…”
Section: Introductionmentioning
confidence: 99%